2019
DOI: 10.1177/2333721419841245
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Leadership and Psychosocial Work Environment on Recipient Satisfaction in Nursing Homes and Home Care

Abstract: This study examines the association between nursing assistants’ assessment of leadership, their psychosocial work environment, and satisfaction among older people receiving care in nursing homes and home care. Cross-sectional surveys were conducted with nursing assistants ( n = 1,132) and people receiving care ( n = 1,535) in 45 nursing homes and 21 home care units. Direct leadership was associated with the psychosocial work environment in nursing homes and home ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Strong leadership in the aged care workforce has been found to contribute to staff intention to remain (Gaudenz et al 2019; Lundgren et al 2019). Among different types of leadership, authentic leadership was considered desirable and identified as ‘those who are deeply aware of how they think and behave and are perceived by others as being aware of their own and others’ values/moral perspectives, knowledge, and strengths; aware of the context in which they operate; and who are confident, hopeful, optimistic, resilient, and of high moral character’ (Avolio et al 2004, p. 4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strong leadership in the aged care workforce has been found to contribute to staff intention to remain (Gaudenz et al 2019; Lundgren et al 2019). Among different types of leadership, authentic leadership was considered desirable and identified as ‘those who are deeply aware of how they think and behave and are perceived by others as being aware of their own and others’ values/moral perspectives, knowledge, and strengths; aware of the context in which they operate; and who are confident, hopeful, optimistic, resilient, and of high moral character’ (Avolio et al 2004, p. 4).…”
Section: Introductionmentioning
confidence: 99%
“…A study by Fallatah et al (2017) in Canada revealed authentic leadership was associated with low job turnover rate and an increased occupational coping level in new graduate nurses. In a large survey study across residential aged care and community care in Sweden, positive staff perceptions were associated with first‐line managers’ leadership and their work environment (Lundgren et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, the effects on job strain in the present study compared with the study by Edvardsson and colleagues (2014) could be discussed from different angles. 16 Firstly, one possible reason for the non-significant findings in this study might be the different context used in the present study. The previous study 18 was conducted in the context of a nursing home, which differs from a home care setting in working conditions for staff regarding opportunities to discuss and learn from each other in their daily work.…”
Section: Discussionmentioning
confidence: 76%
“…15 Previous research also found a positive association between organizational factors such as direct and good leadership and psychosocial work environment, in both contexts of nursing home and home care, and satisfaction among both nurse assistants and older adults. 16 Research also shows that organizational and environmental support, supportive leadership, and a caring climate are associated with a lower level of job strain and stress. 14 These results indicate an essential need for developing and evaluating appropriate interventions providing the educational activities which can create a positive caring and supportive climate, in order to decrease job strain and stress where the nurse assistants are able to provide high-quality care.…”
Section: Introductionmentioning
confidence: 97%
“…Looking at the impact of psychosocial work environment on recipient satisfaction, others find that the psychosocial work environment of nursing assistants and their satisfaction in their work can be increased by good leadership (Lundgren et al, 2019). A study among rural hospitals nurses on the association of work environment evidences that work environment is significantly associated with adverse events (Smith et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%